Copper-catalyzed tandem reaction of 2-haloanilines with thiocarbamoyl chloride: Synthesis of 2-aminobenzothiazoles. Issue 13 (3rd July 2017) - Chang, Cai-Zhu; Xu, Wan; Zeng, Meng-Tian; Liu, Min; Liu, Xing; Zhu, Hui; Dong, Zhi-Bing
ABSTRACT: A simple and efficient protocol for the synthesis of 2-aminobenzothiazoles by a ligand-free copper-catalyzed tandem reaction has been developed. In the presence of CuBr and t -BuOK, a variety of 2-haloanilines (halogen = Br, I) underwent the reaction with thiocarbamoyl chloride efficiently to afford the corresponding 2-aminobenzothiazoles in good yields (83–94%). The features of this method include good yield, cheap catalyst, mild reaction conditions, and broad substrate scope, which make the protocol practical and attractive in the preparation of some potential pharmaceutically active compounds. GRAPHICAL ABSTRACT: